MASTERPLAN SISTEM PENGELOLAAN AIR LIMBAH INDUSTRI DI KAWASAN INDUSTRI BSB CITY, MIJEN-SEMARANG - Ruli Triyani; Wiharyanto Oktiawan; Winardi Dwi Nugraha (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
AbstractIndustrial Park BSB City, Mijen-Semarang has concept as green technology industrial park. There’s 11 industry producting wastewater in existing area at this time. The industrial wastewater flow to drainage without any treatment which make odours at industrial park area. PT Karyadeka Alam Lestari as developer industrial would be like to build wastewater treatment plant which treat all wastewater industries therefore it needs Masterplan Management System Wastewater Industry At Industrial Park BSB City, Mijen-Semarang. This masterplan designing based on industrial park masterplan finished 2025.